Observations of type Ia supernova SN 2020nlb up to 600 days after explosion, and the distance to M85 - Williams, S. C.; Kotak, R.; Lundqvist, P.; Mattila, S.; Mazzali, P. A.; Pastorello, A.; Reguitti, A.; Stritzinger, M. D.; Fiore, A.; Hook, I. M.; Moran, S.; Salmaso, I. (EDP Sciences, 2025)
The type Ia supernova (SN Ia) SN 2020nlb was discovered in the Virgo Cluster galaxy M85 shortly after explosion. Here we present observations that include one of the earliest high-quality spectra and some of the earliest multi-colour photometry of a SN Ia to date. We calculated that SN 2020nlb faded 1.28 ± 0.02 mag in the B band in the first 15 d after maximum brightness. We independently fitted a power-law rise to the early flux in each filter, and found that the optical filters all give a consistent first light date estimate. In contrast to the earliest spectra of SN 2011fe, those of SN 2020nlb show strong absorption features from singly ionised metals, including Fe II and Ti II, indicating lower-excitation ejecta at the earliest times. These earliest spectra show some similarities to maximum-light spectra of 1991bg-like SNe Ia. The spectra of SN 2020nlb then evolve to become hotter and more similar to SN 2011fe as it brightens towards peak. We also obtained a sequence of nebular spectra that extend up to 594 days after maximum light, a phase out to which SNe Ia are rarely followed. The [Fe III]/[Fe II] flux ratio (as measured from emission lines in the optical spectra) begins to fall around 300 days after peak; by the +594 d spectrum, the ionisation balance of the emitting region of the ejecta has shifted dramatically, with [Fe III] by then being completely absent. The final spectrum is almost identical to SN 2011fe at a similar epoch. Comparing our data to other SN Ia nebular spectra, there is a possible trend where SNe that were more luminous at peak tend to have a higher [Fe III]/[Fe II] flux ratio in the nebular phase, but there is a notable outlier in SN 2003hv. Finally, using light-curve fitting on our data, we estimate the distance modulus for M85 to be μ0., =., 30.99 ± 0.19 mag, corresponding to a distance of 15.8+1.4-1.3 Mpc.